1996
DOI: 10.1079/bjn19960193
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nutrition and Eimeria acervulina infection in broiler chickens: diet compositions that improve fat digestion during Eimeria acervulina infection

Abstract: Previously an experimental infection model was developed in which broiler chickens were inoculated with sporulated Eimeria acervufina oocysts at an age of 18 d. The infection resulted in adverse performance results and reduced nutrient digestion. In two new experiments with the infection model effects of diet adjustments on fat digestion were investigated. In the first experiment addition of 0.4 g cholic acidlkg to a diet rich in animal fat resulted in increased fat digestion during the infection. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…Sharma and Fernando (32) observed an accumulation of lipid globules within the duodenal villus epithelial cells of E. acervulina infected birds, indicating that intracellular lipid processing or transport across the basolateral cell membrane of the enterocyte may be compromised. Furthermore, Adams et al (33) reported coccidiosis challenged birds had an improvement in lipid digestion when supplemented with cholic acid, indicating that bile salt synthesis or secretion may be impaired during an infection. In the current experiment, jejunum villi height was not influenced by coccidiosis vaccination at 12 d post-hatch when the greatest impacts of vaccination on nutrient and energy digestibility were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma and Fernando (32) observed an accumulation of lipid globules within the duodenal villus epithelial cells of E. acervulina infected birds, indicating that intracellular lipid processing or transport across the basolateral cell membrane of the enterocyte may be compromised. Furthermore, Adams et al (33) reported coccidiosis challenged birds had an improvement in lipid digestion when supplemented with cholic acid, indicating that bile salt synthesis or secretion may be impaired during an infection. In the current experiment, jejunum villi height was not influenced by coccidiosis vaccination at 12 d post-hatch when the greatest impacts of vaccination on nutrient and energy digestibility were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effect of infection was also reflected in the highest OPG recorded in the excreta collected on post-infection days 6, 8, 9 and 14 and in the lesion score of the duodenum on post-infection day 6. The duodenum is the site of invasion for E. acervulina, which does not cause a drastic increase in mortality, but has a negative impact on the digestion, absorption and assimilation of nutrients (Adams et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Coccidiosis usually reduces body weight gain in broiler chicks as a result of reduced feed intake, digestibility and absorption of macronutrients [17]. It is accepted that weight gain is the more sensitive variable to coccidiosis and anticoccidial treatments [18].…”
Section: Discussionmentioning
confidence: 99%